Study on silica based waste material as partial cement replacement in mortar - Aizat, Gani (Universiti Malaysia Sarawak (UNIMAS), 2014)
The accumulation non-biodegradable waste glass in the overpopulated landfills of developed and developing countries is becoming a serious environmental issue. Numerous researches have been conducted in the past to study the application of waste glass as an alternative material in concrete production. The chemical properties such as high silica content making it an attractive material to be used as partial cement replacement. This research investigates the potential of powdered green waste glass (PGWG) as partial cement replacement in mortar with the research aim of assessing its pozzolanicity in relation to the fineness of the PGWG (>75μm, <75μm ->38μm, and <38μm) and percentage of cement replacement by weight (10%, 20%, 30%, and 40%). Mortar cubes were prepared with water to cement ratio of 0.45, and cement to sand ratio of 0.6. The mortar cubes are cured in room temperature of± 32ᴼC with 90% relative humidity and prepared for compressive strength test. Modified cement paste with the same PGWG size and cement replacement percentage were prepared for FTIR analysis. Mortars and cement paste with 10% cement replacement and PGWG size of <38μm recorded the highest compressive strength test result and display the highest degree of pozzolanic activity from the FTIR analysis respectively.